(untitled) (Scientific journal of the Fergana State University, 2026)
The spread of antibiotic-resistant bacteria poses a serious threat to global public health, leading to a decline in the effectiveness of existing antimicrobial agents. Consequently, the search for new, natural antimicrobial compounds with high biological activity has become an urgent scientific priority. Actinomycetes of the genus Streptomyces are recognized as among the most prominent producers of natural bioactive substances, particularly antibiotics. The aim of this study was to evaluate the antimicrobial activity of a Streptomyces spp. isolate obtained from local soil samples against clinically significant multidrug-resistant pathogens. Identification of the Streptomyces isolates was carried out using standard morphological and physiological-biochemical methods. Antimicrobial activity was assessed using the double-layer agar method and the disk diffusion assay. The results demonstrated that the Streptomyces isolates exhibited pronounced antimicrobial activity against antibiotic-resistant strains. These findings confirm the potential of Streptomyces isolates as a valuable source of new natural antimicrobial agents and highlight their promise for future clinical applications.